Nutrient and anti-nutrient components of raw and processed winged bean seeds(Psophocarpus tetragonolobus) - Igene, F U; Oboh, S 0; Aletor, V A (The Indian Journal of Animal Sciences, 2011)
Experiments were conducted to assess the proximate composition, minerals and anti-nutritional factors, viz. trypsin inhibitor, haemagglutinin, tannin and phytin contents ofraw, boiled, roasted and autoclaved winged bean seeds. The processing techniques adopted had effects on all the parameters assayed. The values obtained for proximate composition with the exception of crude protein and nitrogen free extract were generally close. The ranges were 88.2 - 94. Ig/ 100 g, 35.5 - 47.2g/1 00 g, 9.5 - 10.2gll 00 g, 14.6 - 18.8g/l 00 g, 3.7 - 4.2g/l 00 g, 13.7 - 23.6g/l 00 g, respectively, for dry matter, crude fibre, ether extract, ash and nitrogen free extract. The raw and processed winged bean seeds differed markedly in Na, Ca, Kand Mn contents as indicated by their high coefficients of variation. Generally, the minerals were higher in raw winged bean compared with the processed seeds. Analysis of the toxic factors showed that both raw and autoclaved seeds contained all the anti-nutrients. Trypsin inhibitor activity averaged 41.40 ± 56.06 mg/g (range, 0.0121.07 mg/g), haemagglutinin 2.33 ± 1.25 Hu/mgN (range, 0.0 - 4.0 Hu/mgN), tannin 0.70 ± 0.15g/1 00 g (range, 0.580.94g/ 1 00 g) while phytin averaged 20.47 ± 5.33 mg/g (range, 14.0 - 25.95 mg/g). Trypsin inhibitor was not detected in the boiled winged bean. Roasting resulted in 99.39% destruction oftrypsin inhibitor while haemagglutinin was completely removed. Heat treatments partially affected the levels of tannin and phytin.